The influence of using fermentated rumen content at quail feed to the protein of yolk and albumen of quail eggs - Gesa Cantya Primatara; Mohammad Anam Al Arif; Tita Damayanti Lestari; Widya Paramita Lokapirnasari; Sri Hidanah; Suharsono, Suharsono (Universitas Airlangga, 2024)
Ruminal content is one of slaughterhouse waste that has not been utilized optimally, in fact there are cases where ruminal content are thrown away haphazardly, causing environmental pollution. The nutritional value of ruminal content is relatively high which is caused by the imperfect nutrition absorption do not have much difference with the original nutritional value coming from the cattle feed itself. nutritional value in ruminal content is 8.86% of protein, 2.6% of fat, 28.78% of fiber, 0.55% of phosphor, 18.54% of ash and 10.92% of water content. The aims of this research was to find out whether the usage of fermentation cattle ruminal content in quail’s feed ransom can influence the protein content inside the yolk and albumen of an egg. This research used fermentation cattle ruminal content and divided into four treatments. The first treatment (T0) was only giving formula feed. The second treatment (T1) was Formulation feed (5% fermentated rumen content). The second treatment (T2) was Formulation feed (10% fermentated rumen content). The third treatment (T3) was Formulation feed (15% fermentated rumen content). The experiment design was Completely Randomized Design.